Implementasi Bauran Pemasaran Melalui Live Streaming Di Markerplace Shopee Untuk Meningkatkan Penjualan Pada Himalaya Eyewear - Tiara Feriska; Baby Sri Muniarti Poernomo (JAMBIS : Jurnal Administrasi Bisnis, 2025)
This study aimed to evaluate the marketing strategy implemented by Himalaya Eyewear through livebroadcasts on Shopee, as well as to identify the challenges encountered and the solutions applied toboost sales. This research employed a qualitative method with data collected through observation,interviews, and documentation. The findings revealed that the implemented strategies include selectingthe right broadcast time, offering discounts, bundling promotions, direct interaction with consumers, andcollaboration with influencers. The obstacles faced involved unstable internet connections, limitedproduct stock, and insufficient content during live streaming.Keywords: Digital Marketing, Live Streaming, E-Commerce, Shopee, Himalaya Eyewear